Survey of Plasmodium in the golden-headed lion tamarin (Leontopithecus chrysomelas) living in urban Atlantic forest in Rio de Janeiro, Brazil. (December 2016) - Aitken, Elizabeth; Bueno, Marina; Santos Ortolan, Luana; Alvaréz, José; Pissinatti, Alcides; Kierulff, Maria; Catão-Dias, José; Epiphanio, Sabrina
Abstract Background Communicating the presence of potential zoonotic pathogens such asPlasmodium spp. in wild animals is important for developing both animal and human health policies. Methods The translocation of an exotic and invasive population ofLeontopithecus chrysomelas (golden-headed lion tamarins) required the screening of these animals for specific pathogens. This studies objective was to investigatePlasmodium spp. infection in theL. chrysomelas, both to know its prevalence in these animals in the local area and to minimize the risk of pathogens being translocated to the destination site. To investigatePlasmodium spp. infection, blood samples from 268 animals were assessed for the presence ofPlasmodium spp. by genus-specific PCR and stained thick and thin blood smears were examined by light microscopy. Data of human malaria infection in the studied region was also assembled from SINAN (Diseases Information System Notification—Ministry of Health of Brazil). Results Results from the PCR and microscopy were all negative and suggested that noL. chrysomelas was infected withPlasmodium spp. Analysis of SINAN data showed that malaria transmission is present among the human population in the studied region. Conclusions This study is the first to provide information onPlasmodium spp. infection inL. chrysomelas. Plasmodium spp. infection of this species is rare or absent though malaria parasites circulate in the region. In addition, there is minimal risk of translocatingPlasmodium spp. infected animals to the destination site.